Linear reduction of propagules of Ralstonia solanacearum in soil by cake and chemicals - S. KUMAR, J.P. SHARMA* and (Indian Phytopathology, 2009)
In Alfisol of east India plateau soil application of karanj (Pongamia glabra) cake, bleaching powder (CaClO3), lime (CaCO3) and seedling dip and spray of streptocycline resulted in reduction of initial population of Ralstonia solanacearum (R.s.) in soil in post monsoon seasons of 1998-99 to 2001-02. The percent reductions in initial population of R.s. noted at 90 d after transplanting of tomato were 30.5 and 33.2 at 10 and 20 q karanj (Pongamia) cake ha-1; 31.9 and 35.0 at 30 and 45 kg bleaching powder ha-1; 28.6 and 27.9 at seedling dip and spray of streptocycline (500 ppm) and a mild reduction of 18.7 at 25 q lime ha-1 . The natural control process resulted in to 14.6% reduction as evident from untreated control. Based in linear equation reduction of initial population, it is suggested that bleaching powder and karanj cake are stronger bacteriostatic substance than lime and streptocycline.